Efficiency and Financial Performance of BAZNAS: A Stochastic Frontier and International Standard of Zakat Management Approach - Fadhilah, Zuhdiyyah Rifda Nur; Fitanto, Bahtiar (Universitas Airlangga, 2025)
Indonesia as a country with a majority Muslim population has a high potential for zakat. However, this is inversely proportional to the realization of the receipt of zakat funds. In addition, the balance of zakat funds in BAZNAS RI is increasing per year. This indicates that the institution is increasingly inefficient in managing its funds. This study aims to measure the level of efficiency and financial performance of zakat institutions using the SFA method and the ISZM model at BAZNAS RI in 2012-2023. The result of SFA analysis shows that the average efficiency level of zakat revenue is 95.86% and the efficiency of zakat distribution is 91.76%. The efficiency of zakat revenue is higher than that of zakat distribution because it is supported by digitalization optimization, while the efficiency of zakat distribution is constrained by geographical barriers and complex operational costs. ISZM analysis shows that the ratio of operational, program, and collection costs is relatively efficient, but the collection efficiency ratio is still quite efficient. In terms of capacity, the main income growth and program expenses show good performance, but the working capital ratio is not good. The results of this study are expected to be a reference for zakat institutions in improving their efficiency and performance as well as for future researchers who will examine the efficiency of zakat institutions.